2010
DOI: 10.1242/dev.039404
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional control of stem cell maintenance in theDrosophilaintestine

Abstract: SUMMARYAdult stem cells maintain tissue homeostasis by controlling the proper balance of stem cell self-renewal and differentiation. The adult midgut of Drosophila contains multipotent intestinal stem cells (ISCs) that self-renew and produce differentiated progeny. Control of ISC identity and maintenance is poorly understood. Here we find that transcriptional repression of Notch target genes by a Hairless-Suppressor of Hairless complex is required for ISC maintenance, and identify genes of the Enhancer of spli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
181
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(204 citation statements)
references
References 64 publications
(92 reference statements)
15
181
0
Order By: Relevance
“…The HES/HEY genes are not, however, the only targets of Notch signaling as in many tissues loss of HES/HEY genes does not recapitulate all of the phenotypes of loss of Notch activity indicating the existence of addition target genes [54][55][56][57][58]. Indeed, there are a large number of cellspecific Notch targets [59,60].…”
Section: Other Notch Transcriptional Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HES/HEY genes are not, however, the only targets of Notch signaling as in many tissues loss of HES/HEY genes does not recapitulate all of the phenotypes of loss of Notch activity indicating the existence of addition target genes [54][55][56][57][58]. Indeed, there are a large number of cellspecific Notch targets [59,60].…”
Section: Other Notch Transcriptional Targetsmentioning
confidence: 99%
“…In addition, Notch target genes are also controlled through transcriptional repression [54]. Loss of the co-repressor Hairless in the ISC results in loss of ISCs, at least in part by its terminal differentiation, suggesting that Hairless acts in combination with Su(H)/RBP-Jk to keep the expression of Notch target genes repressed in the ISC [54].…”
Section: Intestinal Stem Cells (Isc) Of Drosophila Melanogaster: Notcmentioning
confidence: 99%
See 1 more Smart Citation
“…The larval midgut is an endothelial tube containing two differentiated cell types, namely, enterocytes and enteroendocrine cells, which arise from stem cell crypts located within the gut and differentiate into either cell type in a Notch signaling pathway-dependant manner [18,19]. Depending on position cues within the gut tube, the enterocytes develop a wide variety of morphologies and functions and represent the majority of the cells within the midgut.…”
Section: Drosophila Gut Developmentmentioning
confidence: 99%
“…Functionally, FOXD3 has been implicated in the control of differentiation in multiple systems, mostly preventing appropriate maturation [40,[112][113][114][115]. Interestingly, accumulated data suggest that this mode of action, through cell fate restriction, is a central hallmark of stem cells in general [116][117][118][119]. As such, it has been shown that ectopic expression of FOXD3 in the neural tube promotes a NC-like phenotype and continued expression of FOXD3 in migrating NCCs interferes with their subsequent differentiation in NC derivatives [112,113], suggesting that FOXD3 may play a critical role in establishing or maintaining proliferating and self-renewing progenitor cell populations.…”
Section: The Multipotent Schwann Cell Precursormentioning
confidence: 99%